THE FORMED IMAGE OF ŠIAULIAI CITY: THE ASPIRATION OF THE CITY MUNICIPALITY AND ITS REFLECTION IN THE LOCAL MEDIA - Kuliavcevaitė, Santa; Kulbeckienė, Gintarė; Litevkienė, Nijolė (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The essence of the research topics is that Šiauliai does not have the city-specific image: the aspiration is to form the vision of the city of the Sun, linking it with the idea of a safe, open, and vibrant city. Therefore, it was sought to find out what image of the city was formed by Šiauliai city municipality and what image of the city was revealed in the local media. It turned out that the directions of the image of Šiauliai city formed by Šiauliai city municipality and the weekly “Etaplius” coincided. It was found that the weekly “Etaplius” formed a positive image of Šiauliai city in the press; therefore, it can be assumed that the local media itself seeks to contribute to the formation of the city’s favourable image in the public space. Key words: city, image, formation, municipality, local media.